PENGARUH PERAN ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA SELAMA PANDEMI COVID-19 PADA MATA PELAJARAN IPS DI MTS DARUL FALAH TANGGA BATU KABUPATEN ROKAN HILIR - Ayu Kartika; Suarman Suarman; Hendripides Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Absract : This study aims to analyze the influence of the role of parents on students' learning motivation during the Covid-19 pandemic on ips subjects in MTs Darul Falah Tangga Batu Rokan Hilir Regency. The population in this study was all students of MTs Darul Falah Tangga Batu. Data collection techniques are conducted using questionnaires to obtain data on the role of parents and students' learning motivations. The sample was taken by 94 students from 146 students, using stratified random sampling proportionate technique to determine the number of samples taken. The collected data is then tabulated and analyzed using simple linear regression. The results showed the value of Asymp. Sig (2-tailed) on the parent role variable was 0.486 and the learning motivation was 0.115. It shows that if the sig value > 0.05, then it can be concluded that there is an influence on the role of parents on students' learning motivation during the Covid-19 pandemic in ips subjects in MTs Darul Falah Tangga Batu Rokan Hilir regency and distribution normally. Based on this description, parents are encouraged to show more role in paying attention and encouraging their children to have optimal motivation in following the learning process in school, especially in Covid-19 conditions.Key words : Parent Role, Learning Motivation